Step 1: Compute the first derivative \( f'(x) \).
The given function is:
\[
f(x) = \frac{4 \sin x}{2 + \cos x} - x
\]
Differentiating term by term:
\[
f'(x) = \frac{(2 + \cos x)(4 \cos x) - (4 \sin x)(-\sin x)}{(2 + \cos x)^2} - 1
\]
Step 2: Simplify the derivative.
\[
f'(x) = \frac{8 \cos x + 4 \cos^2 x + 4 \sin^2 x}{(2 + \cos x)^2} - 1
\]
Using \( \sin^2 x + \cos^2 x = 1 \), we rewrite:
\[
f'(x) = \frac{8 \cos x + 4}{(2 + \cos x)^2} - 1
\]
\[
= \frac{8 \cos x + 4 - (2 + \cos x)^2}{(2 + \cos x)^2}
\]
Expanding \( (2 + \cos x)^2 = 4 + 4 \cos x + \cos^2 x \):
\[
f'(x) = \frac{8 \cos x + 4 - (4 + 4 \cos x + \cos^2 x)}{(2 + \cos x)^2}
\]
\[
= \frac{8 \cos x + 4 - 4 - 4 \cos x - \cos^2 x}{(2 + \cos x)^2}
\]
\[
= \frac{4 \cos x - \cos^2 x}{(2 + \cos x)^2}
\]
Step 3: Check positivity in \( \left[ 0, \frac{\pi}{2} \right] \).
For \( x \in \left[ 0, \frac{\pi}{2} \right] \), we know that \( \cos x \geq 0 \), so:
\[
f'(x) = \frac{\cos x (4 - \cos x)}{(2 + \cos x)^2} \geq 0
\]
since both \( \cos x \) and \( (4 - \cos x) \) are non-negative.
Conclusion:
Since \( f'(x) \geq 0 \) for all \( x \) in \( \left[ 0, \frac{\pi}{2} \right] \), \( f(x) \) is an increasing function in this interval.